Ground Penetrating Radar Algorithm to Sense the Depth of Blood Clot in Microwave Head Imaging - Kandasamy, Lalitha; J., Manjula (Current Medical Imaging, 2022)
Background: Microwave imaging is one of the emerging non-invasive portable imaging techniques, which uses nonionized radiations to take a detailed view of biological tissues in the microwave frequency range. Brain stroke is an emergency caused by the interruption of the blood supply into parts of the brain, leading to the loss of millions of brain cells. Imaging plays a major role in stroke diagnosis for prompt treatment. Objective: This work proposes a computationally efficient algorithm called the GPR algorithm to locate the blood clot with a size of 10 mm in microwave images. Methods: The electromagnetic waves are radiated, and backscattered reflections are received by Antipodal Vivaldi antenna with the parasitic patch (48 mm*21 mm). The received signals are converted to a planar 2D image, and the depth of the blood clot is identified from the B-scan image. The novelty of this work lies in applying the GPR algorithm for the accurate positioning of a blood clot in a multilayered head tissue. Results: The proposed system is effectively demonstrated using a 3D M.E.M. simulator, and simulated results are verified in a Vector network analyzer (E8363B) with an experimental setup. Conclusion: This is an alternative safe imaging modality compared to present imaging systems (T.C.T. and MRI).
Keywords: depth of blood clot